Restructuring House Financing (KPR) Due to the Impact of the Covid-19 Pandemic at Pt Bank Tabungan Negara (Persero) Tbk KC Banyuwangi - Agnes Pasaribu; Wisnu Ardytia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Banks as financial institutions can collect funds from the public and channel them back to the community in the form of credit. One of the services provided by BTN KC Banyuwangi is a home financing loan. There are times when credit is disbursed by troubled banks due to various factors, one of which is being affected by the COVID-19 pandemic, causing debtor customers to default, so credit restructuring is needed. The question of this research is how to apply the regulation of POJK No. 11/2020 to the restructuring of housing loans at PT BTN KC Banyuwangi and the legal consequences of the restructured credit agreements. This research uses empirical and normative juridical methods, where the application of research is through literature studies, documentation and interviews. Data processing performs editing, coding and analysis. The results of the study concluded that the restructuring of KPR BTN KC Banyuwangi was carried out referring to PBI Number 8/2/2006 and POJK Number 11/2020, namely by taking into account the quality of productive assets, customer good faith and selecting the right rescue strategy target, namely the period of delaying payments for 6 month to 1 year. The legal consequence of the addendum to the financing contract is that it is in addition to the initial financing contract, so that the provision of the initial financing contract is still enforced as a binding condition for the parties.